2019
DOI: 10.1111/fwb.13285
|View full text |Cite
|
Sign up to set email alerts
|

Structural equation models suggest that bottom‐up processes override top‐down processes in boreal pikeperch (Sander lucioperca) lakes

Abstract: Inter‐relations between water quality and piscivore populations have remained poorly studied but their quantification is crucial for the ecosystem‐based management of inland waters. Here, we aimed to estimate the relative strength of bottom‐up and top‐down trophic interactions between water quality and fish community composition using a comparative approach. Our main hypothesis was that lakes with an abundant piscivore (mainly pikeperch, Sander lucioperca, Percidae) stock would have better water quality than s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…The feeding on both zooplankton and benthic macroinvertebrates by omnivorous fish may weaken top‐down cascades on pelagic zooplankton and phytoplankton relative to bottom‐up cascades where high phytoplankton biomasses induce high zooplankton biomasses, and omnivorous fish use this resource directly. The effect of piscivorous fish on top‐down and bottom‐up cascades was not significant, confirming earlier studies showing that the control of omnivorous fishes by piscivore predation is usually weak (Mehner ; Mehner et al ; Kokkonen et al ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The feeding on both zooplankton and benthic macroinvertebrates by omnivorous fish may weaken top‐down cascades on pelagic zooplankton and phytoplankton relative to bottom‐up cascades where high phytoplankton biomasses induce high zooplankton biomasses, and omnivorous fish use this resource directly. The effect of piscivorous fish on top‐down and bottom‐up cascades was not significant, confirming earlier studies showing that the control of omnivorous fishes by piscivore predation is usually weak (Mehner ; Mehner et al ; Kokkonen et al ).…”
Section: Discussionsupporting
confidence: 85%
“…In a study focusing on the effect of piscivores on prey density and size and indirectly on Chl a in more than 60 lakes in northern Germany, Mehner () found a weak top‐down control of fish on Chl a . In a recent study in 138 Finnish oligo‐eutrophic lakes populated by piscivorous pikeperch ( Sander lucioperca ), Kokkonen et al () demonstrated that bottom‐up effects of phytoplankton on fish were much stronger than the top‐down effects by fish on phytoplankton. We suggest that our results complement these earlier studies and support the suggestion of a relatively weak top‐down effect of fish on phytoplankton biomass in across‐lake comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…We stress that this question is not equivalent to asking whether the system is bottom-up or top-down controlled (as in e.g. Kokkonen et al, 2019), but whether bottom-up or top-down dynamical effects, relevant to predict trophic cascades, can be seen in the biomass distribution.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…We stress that this question is not equivalent to asking whether the system is bottom‐up or top‐down controlled (as in e.g. Kokkonen et al ., 2019), but whether bottom‐up or top‐down dynamical effects, relevant to predict trophic cascades, can be seen in the biomass distribution.…”
Section: Discussionmentioning
confidence: 99%